Withdrawal from an opioid induces a transferable memory trace in the cerebrospinal fluid. Issue 12 (December 2019) - Drdla-Schutting, Ruth; Heinl, Céline; Hadschieff, Viktoria; Sandkühler, Jürgen
Abstract : Abstract: Opioids are the most powerful analgesics available to date. However, they may also induce adverse effects including paradoxical opioid-induced hyperalgesia. A mechanism that might underlie opioid-induced hyperalgesia is the amplification of synaptic strength at spinal C-fibre synapses after withdrawal from systemic opioids such as remifentanil ("opioid-withdrawal long-term potentiation [LTP]"). Here, we show that both the induction as well as the maintenance of opioid-withdrawal LTP were abolished by pharmacological blockade of spinal glial cells. By contrast, the blockade of TLR4 had no effect on the induction of opioid-withdrawal LTP. D-serine, which may be released upon glial cell activation, was necessary for withdrawal LTP. D-serine is the dominant coagonist for neuronal NMDA receptors, which are required for the amplification of synaptic strength on remifentanil withdrawal. Unexpectedly, opioid-withdrawal LTP was transferable through the cerebrospinal fluid between animals. This suggests that glial-cell-derived mediators accumulate in the extracellular space and reach the cerebrospinal fluid at biologically active concentrations, thereby creating a soluble memory trace that is transferable to another animal ("transfer LTP"). When we enzymatically degraded D-serine in the superfusate, LTP could no longer be transferred. Transfer LTP was insensitive to pharmacological blockade of glial cells in the recipient animal, thus representing a rare form of glial cell-independent LTP in the spinal cord. Abstract : Withdrawal from an opioid induces synaptic plasticity in pain pathways, which is transferable through the cerebrospinal fluid between animals.